Transcriptome Analysis of Gene Expression in Dermacoccus abyssi HZAU 226 under Lysozyme Stress - Zhang, Xinshuai (Microorganisms, 2020)
Lysozyme acts as a kind of cationic antimicrobial protein and effectively hydrolyzes bacterial peptidoglycan to have a bactericidal effect, which also plays an important role in protecting eggs from microbial contamination. Dermacoccus abyssi HZAU 226, a Gram-positive bacterium isolated from spoiled eggs, has egg white and lysozyme tolerance, but its survival mechanism is unknown, especially from a transcriptomics point of view. In this study, the high lysozyme tolerance of D. abyssi HZAU 226 was characterized by three independent experiments, and then the Illumina RNA-seq was used to compare the transcriptional profiles of this strain in Luria–Bertani (LB) medium with and without 5 mg/mL lysozyme to identify differentially expressed genes (DEGs); 1024 DEGs were identified by expression analysis, including 544 up-regulated genes and 480 down-regulated genes in response to lysozyme treatment. The functional annotation analysis results of DEGs showed that these genes were mainly involved in glutathione biosynthesis and metabolism, ion transport, energy metabolism pathways, and peptidoglycan biosynthesis. This study is the first report of bacterial-related lysozyme RNA-seq, and our results help in understanding the lysozyme-tolerance mechanism of bacteria from a new perspective and provide transcriptome resources for subsequent research in related fields.